Evaluation of Physiological and Biochemical Parameters in Chronic Kidney Disease Patients at AL Assabah Dialysis Center in Libya - Abdulrzaq Yousef; Ismael Almlyan (المجلة الأفروآسيوية للبحث العلمي, 2025)
Kidney failure is a health problem affecting people worldwide. Hematological problems in dialysis patients are associated with altered physiological and biochemical parameters in patients with renal failure. This study aimed to measure changes in physiological and biochemical parameters in patients undergoing dialysis. The study was conducted from July 2024 to August 2024 at the Al-Assabah Dialysis Center. It included 37 patients with kidney failure and 20 healthy individuals. Biochemical and hematological parameters, including blood sugar, cholesterol, triglycerides, urea, creatinine, uric acid, phosphorus, hemoglobin, platelets, red blood cells, and white blood cells, were examined and compared with those in healthy individuals. The study revealed that 73% of patients were men, with the majority falling within the 30- to 40-year-old age range. The study revealed statistical significance between the two groups in hemoglobin levels (P = 0.002) and red blood cell count (P < 0.000). The study also showed differences between the two groups in urea and creatinine levels. The study found that blood sugar levels were normal, and there was no significant difference between the sexes or the two groups, although men represent the majority of infected cases in the study population. The study concluded that there is a significant difference in the levels of biochemical parameters, hemoglobin, and red blood cell count in kidney failure patients compared to the healthy group, and that males are more susceptible to kidney failure.